2019
DOI: 10.1002/chir.23130
|View full text |Cite
|
Sign up to set email alerts
|

Helicity of perfluoroalkyl chains controlled by the self‐assembly of the Ala‐Ala dipeptides

Abstract: Four Ala‐Ala dipeptides with a perfluoroalkyl chain at the N‐terminal were synthesized. They were able to self‐assemble into helical nanofibers and/or twisted nanobelts in a mixture of DMSO/H2O. The handedness of nanofibers and nanobelts was controlled by the chirality of the alanine at the N‐terminal. The stacking handedness of the phenylene groups and the helicity of the perfluoroalkyl chain were studied using circular dichroism spectroscopy and vibrational circular dichroism, respectively. The chirality of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 46 publications
(96 reference statements)
0
7
0
Order By: Relevance
“…Also, Zhang et al . [ 37 ] reported that AA dipeptides bearing a perfluroalkyl chain connected with a phenyl group yielded a 1D helical nanofibers in DMSO/H 2 O. Despite the difference in the C‐terminal groups between previous studies (carboxyl) and this study (hydrazide), one small aromatic group, such as the nitrophenyl group ( NPmoc ) at N‐terminus of the AA dipeptide scaffold (instead of larger aromatic group such as Fmoc), may be not enough to induce (1D) controlled growth of self‐assembled structures but can induce uncontrolled multidimensional growth under the conditions we observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, Zhang et al . [ 37 ] reported that AA dipeptides bearing a perfluroalkyl chain connected with a phenyl group yielded a 1D helical nanofibers in DMSO/H 2 O. Despite the difference in the C‐terminal groups between previous studies (carboxyl) and this study (hydrazide), one small aromatic group, such as the nitrophenyl group ( NPmoc ) at N‐terminus of the AA dipeptide scaffold (instead of larger aromatic group such as Fmoc), may be not enough to induce (1D) controlled growth of self‐assembled structures but can induce uncontrolled multidimensional growth under the conditions we observed.…”
Section: Resultsmentioning
confidence: 99%
“…As one of pioneering works, Zhang et al [36] reported that Fmoc-AA-OH gives rise to a hydrogel through the formation of 1D fibrous structures. Also, Zhang et al [37] reported that AA dipeptides bearing a perfluroalkyl chain connected…”
Section: Morphology Of Self-assembled Structures Of Peptide Hydrazidesmentioning
confidence: 99%
“…In particular, self-assembling short-peptides represent cheap building blocks for large-scale production, and with overall promising properties in terms of bioactivity [ 2 ] and biocompatibility to achieve functional materials [ 3 , 4 ]. The large chemical diversity they provide ensures continuous advancements, and even considering just the publications in the last couple of years, numerous regard self-assembling tripeptides [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] and dipeptides [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Furthermore, the study of such simple systems could advance the understanding of prebiotic chemistry, relative to the potential role of peptide-based organized structures in the emergence of catalytic activity [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…26 The solid-state structure of cyclo LD-diphenylalanine 27 and the helicity of Ala-Ala dipeptides with a perfluoroalkyl chain at the N-terminal were studied using VCD. 28 Representative VCD couplet patterns for the amide I and amide II vibrational modes of polypeptides have been presented in some previous studies. [29][30][31] Moreover, VCD is usually combined with computational models based on density functional theory (DFT).…”
Section: Introductionmentioning
confidence: 99%
“…The stereochemical effects of the self‐assembly of tripeptide Phe‐Phe‐Phe were revealed by solid‐state VCD 26 . The solid‐state structure of cyclo ld ‐diphenylalanine 27 and the helicity of Ala‐Ala dipeptides with a perfluoroalkyl chain at the N‐terminal were studied using VCD 28 . Representative VCD couplet patterns for the amide I and amide II vibrational modes of polypeptides have been presented in some previous studies 29–31 .…”
Section: Introductionmentioning
confidence: 99%